Toward a holistic view of warfare - Vicente, João (2011)
The lethality, precision, and global reach of the American way of war has changed the modern character of warfare, allowing the US to fight wars with fewer casualties and destruction, creating the general perception that conflicts are acceptable, safe, and clean. However, future emergence of a multipolar world, and the rise of US’s peer competitors with contradictory national interests, will increase the risks of conflict. Given the limited effectiveness of conventional warfare against the overwhelming conventional power of American military forces, future peer competitors will seek to dislocate its strengths. Furthermore, future trends such as the proliferation and affordability of commercial technologies, the increasing civilianization of war, and the importance of global media, will provide the leverage that asymmetric competitors can use to challenge the US outside the traditional military domain. Such changes will require professional military practitioners to have a better understanding of the nature of future warfare.